2013
DOI: 10.1136/jech-2012-201718
|View full text |Cite
|
Sign up to set email alerts
|

Parental use of antidepressant medication and family type in the risk for incident psychiatric morbidity in offspring

Abstract: Parental depression as measured by antidepressant use, and single parenthood pose a risk for psychiatric morbidity in offspring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…Parental PTSD, alone or together with TBI, appeared to account for the largest increases in children's psychiatric medication usage. These findings are consistent with the results of studies showing that children of parents with mental health diagnoses are more likely to use psychiatric medications 55 and that children of parents with PTSD are more likely to have internalizing and externalizing symptoms. 56 Previous research has indicated that parents with children in the home have more severe symptoms of and are more likely to receive care for PTSD more than nonparents.…”
Section: Discussionsupporting
confidence: 90%
“…Parental PTSD, alone or together with TBI, appeared to account for the largest increases in children's psychiatric medication usage. These findings are consistent with the results of studies showing that children of parents with mental health diagnoses are more likely to use psychiatric medications 55 and that children of parents with PTSD are more likely to have internalizing and externalizing symptoms. 56 Previous research has indicated that parents with children in the home have more severe symptoms of and are more likely to receive care for PTSD more than nonparents.…”
Section: Discussionsupporting
confidence: 90%
“…Given the risk of the intergenerational transmission of mental health problems in children being raised by two depressed parents (see Nomura et al 2001; Lieb et al . 2002; Joutsenniemi et al 2013), there is an imperative to identify at-risk families and intervene at an early stage. Greater exploration of the associations between paternal depression and the mental health and well-being of both mother and child were beyond the scope of the present study but merit further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Joutsenniemi et al . (2013) found a twofold increased risk of mental health problems in offspring who were raised in households where both parents were taking antidepressants. Children of depressed parents are also at increased risk of substance use and anxiety disorder (Lieb et al .…”
Section: Introductionmentioning
confidence: 99%